PENGARUH KOMITMEN ORGANISASIONAL TERHADAP PRESTASI KERJA KARYAWAN PADA PT. PERMODALAN NASIONAL MADANI (PERSERO) CABANG MANADO - Sengkeh, Devi; Rumawas, W.; Tumbel, Tinneke M. (JURNAL ADMINISTRASI BISNIS, 2017)
The background of this research indicates that the low organizational commitment of employees affects that the low performance of work, so the problem studied in this research is: How big influence Organizational Commitment to Employee Work Achievement at PT. Permodalan Nasional Madani (Persero) Branch ManadoEmployee commitment to the organization shown by employee characteristics is (1) employees are more concerned with personal interests than the company’s interest in completing the target work, where employees are more focused on personal issues. (2) less maximize the contribution of his work as part of the organization as a whole in carrying out its duties and obligations; (3) lackof cooperation among employees in solving the problem. This shows that the low organizational commitment of employees resulted in the likelihood of job performance at PT. Permodalan Nasional Madani (Persero) Branch Manado, so the higher one’s commitment to the task the higher the performance will be generated. In this research the method used is quantitative method, by using correlation analysis approach and simple linear regression with data analysis technique used is Pearson Product Moment Correlation Analysis (PPM). Based on the calculation of Pearson Product Moment correlation, organizational commitment contributed 97.6% while the remaining 2.4% was a contribution from other variables. And there is a significant influence between Organizational Commitment to Employee Performance at PT. Permodalan Nasional Madani (Persero) Branch Manado. While the calculation results of simple linear regression analysis with the result fhitung â‰¥ ftabel, or 2787.82 â‰¥ 2.05, thus reject Ho, which means a significant effect. This means that Organizational Commitment has a significant and linearly influence on Employee Work Performance at PT. Permodalan Nasional Madani (Persero) Branch Manado. There is a significant influence between organizational commitment employees affect the performance of work at PT. Permodalan Nasional Madani (Persero) Branch Manado. It is recommended to always pay attention to employee performance for the effectiveness and efficiency of PT. Permodalan Nasional Madani (Persero) Manado Branch, so as to maintain its reputation as one of the reliable and trust worthy capital business entities. Keywords : Organizational Commitment, Employee Performance.